Diabolical Doubt: The Peculiar Account of Brother Bernard's Demonic Possession in Jordan of Saxony's Libellus. (16th June 2016) - Watts, Steven
Abstract : Jordan of Saxony's Libellus, first produced in 1233, has struck scholars as an unwieldy combination of hagiography and early Dominican history. Compounding its somewhat awkward nature are its various jumps in chronology and idiosyncratic biographical asides. Perhaps the most idiosyncratic of them all is Jordan's lengthy account of Brother Bernard's demonic possession. While this account provides the setting for the institution of the Dominican custom of chanting the Salve Regina after compline, it is difficult to see at first glance what benefit the story as told would have had for Jordan's audience. Upon closer inspection, however, some method appears in the madness. From a pedagogical point of view – the Libellus is described in the mid-thirteenth-century Vitas fratrum as a journal Jordan read to novices in Paris – the revelation of Jordan's various attempts at identifying the demon's wiles suggests a master willing to allow his students to witness his own doubts about how to proceed. Furthermore, the possessed brother shows a remarkable capacity to imitate ideals central to Dominican identity, in so far as Jordan reveals such ideals in his Libellus : a master of theology, a charismatic preacher and a prospective saint. This essay offers a close analysis of this perplexing narrative, describing the significance of the various demonic phenomena and Jordan's reactions to them, and reflecting on the pedagogical implications of the portrayal of Jordan's uncertainty.